Bi-metal interface-mediated defects distribution in neon ion bombarded Cu/Ag nanocomposites. (October 2019) - Wang, Min; Beyerlein, Irene J.; Zhang, Jian; Han, Wei-Zhong
Abstract: Bi-metal interfaces act as sinks for radiation defects and hence play an important role in the design of radiation-resistant materials. Here, we report that under neon ion bombardment, the hetero-twin Cu/Ag interface serves as a vacancy pump, transferring vacancies from Cu to Ag, a mechanism first observed under helium radiation ( Acta Materialia 160 (2018) 211–223 ). By comparing helium and neon ion irradiated samples, we reveal that helium likes to aggregate with vacancies and slow down the recombination rate of radiation-induced interstitials and vacancies, which leads to significant swelling, radiation-enhanced diffusion and a stronger vacancy pump effect. Graphical abstract: Unlabelled Image